Estimating self-performance when making complex decisions - Xiaping Lu; Carsten Murawski; Peter Bossaerts; Shinsuke Suzuki (Scientific Reports)
Abstract Metacognition, the ability to monitor and reflect on our own mental states, enables us to assess our performance at different levels – from confidence in individual decisions to overall self-performance estimates (SPEs). It plays a particularly important part in computationally complex decisions that require a high level of cognitive resources, as the allocation of such limited resources presumably is based on metacognitive evaluations. However, little is known about metacognition in complex decisions, in particular, how people construct SPEs. Here, we examined how SPEs are modulated by task difficulty and feedback in cognitively complex economic decision-making, with reference to simple perceptual decision-making. We found that, in both types of decision-making, participants’ objective performance was only affected by task difficulty but not by the presence of feedback. In complex economic decision-making, participants had lower SPEs in the absence of feedback (compared to the presence of feedback) in easy trials only but not in hard trials, while in simple perceptual decision-making, SPEs were lower in the absence of feedback in both easy and hard trials. Our findings suggest that people estimate their performance in complex economic decision-making through distinct metacognitive mechanisms for easy and hard instances.